Development of kombucha beverage derived from aquilaria malaccensis tea infused with pineapple and mint - Looi, Tze San (2022)
Kombucha is a popular functional beverage known for its health benefits. The production of kombucha involves fermenting a tea with a symbiotic culture of bacteria and yeasts (SCOBY). The common types of tea that are used as the base of kombucha are black tea and green tea of Camellia sinensis. The research interests to explore the potential of utilizing locally available plants as the tea base for kombucha is expanding. In tropical countries, farmers are capitalising on the leaves of Aquilaria tree by making it into a tea drink and it is commonly known as agarwood tea. This tea is known to contain pharmacological and antioxidant properties. Up to date, there were limited studies utilizing agarwood tea as the base for kombucha beverages with the combination of pineapple and mint. This leads to the objective of this study to evaluate the difference in terms of the overall physicochemical, antioxidant properties, and consumer acceptance between agarwood tea base kombucha and green tea base kombucha. The kombucha was prepared by fermenting the sweetened tea with a SCOBY for 7 days, before the addition of flavouring and fermenting it again for another 3 days. The tests performed were the pH, Brix value, total titratable acidity, DPPH inhibition assay and total phenolic content. A sensory evaluation was also conducted with 30 panelists to determine consumer acceptance of the newly developed kombucha. It was found that the pH, total soluble solids, and DPPH inhibition between agarwood tea and green tea kombucha were similar by the end of fermentation. Although the total phenolic content of green tea kombucha was significantly higher (p < 0.05) than agarwood tea kombucha, the latter showed a higher taste acceptance by panelists. Hence, this study paves the way for the use of Aquilaria leaves in the development of kombucha.